WHAT IS SO SCARY ABOUT LEARNING ENGLISH? INVESTIGATING LANGUAGE ANXIETY AMONG FILIPINO COLLEGE STUDENTS - Al Ryanne Gabonada Gatcho; BONJOVI HASSAN HAJAN (Premise: Journal of English Education and Applied Linguistics, 2019)
Learning English as a foreign/second language is never a straightforward process. Several constraints may come along the way that tend to hinder students’ learning. Studies have shown that the successes and failures of L2 learners in an English language classroom are dependent upon various psychological and social factors including anxiety. This study examined the English language learning anxiety of Filipino college students. The Foreign Language Classroom Anxiety survey adapted from Horwitz, Horwitz and Cope (1986) was administered to a group of 150 students randomly selected from 5 programs at a private university in the Philippines to identify students’ anxiety level in terms of fear of negative evaluation, communication apprehension, fear of test, and anxiety of English class and to determine which factor is most probable to cause anxiety among them.. The results indicated that the students expressed different levels of anxiety among the four factors as majority provided answers ranging from neutral to strongly agree. However, it was discovered that fear of negative evaluation and communication apprehension were the most probable to cause anxiety among them. The study offers practical implications as to how L2 teachers can help students overcome their English anxiety and thus be successful in the learning of the target language.